Sistem Pendeteksi Ancaman Keamanan Rumah Dengan Menggunakan Telegram Berbasis Internet Of Things - Eka Prasetiyo, Fadilah; Setiyadi, Didik Setiyadi (STMIK IKMI Cirebon, 2021)
The comfort and safety of a house is the dream of any home owner, even a house that has a modern security system will be more in demand than a house with an ordinary security system. By utilizing existing technology, it is possible to create an excellent security system from theft and fire. In order to overcome these problems, a prototype of a security threat detection system was made using telegrams based on the internet of things. This can minimize the inconvenience of home owners when they are not at home in a long time, such as the owner of the house going out of town or abroad. The design of this smart home uses the NodeMCU ESP8266 Wifi Module as a controller, the telegram application as a notification when an unknown person opens a door or window, and when a fire occurs. The sensor used to detect the security of burglars is a Magnetic Door Switch, this sensor is placed on doors and windows. The sensor used to detect fire indications is the Flame Sensor which is placed on the ceiling of the house